Explosion mitigation using aqueous solutions of water and flame inhibitors - Kees van Wingerden; Morten Holme; Kjetil Olsen; Dirk Roosendans; Pol Hoorelbeke (Chemical Engineering Transactions, 2019)
The current paper describes results of tests performed with aqueous solutions of flame inhibitors at a larger-scale. Two sets of experiments were performed: experiments using superheated aqueous solutions and experiments where aqueous solutions were dispersed using a water deluge system. The main aim of these experiments was to verify the effects seen on small-scale on a larger scale to verify the possibility of using this mitigation technique on industrial scale. Both sets of experiments were performed in a congested 50m3 chamber provided with explosion venting. To generate water-mists directly at a larger-scale in sufficiently high concentrations a dispersion of superheated aqueous solutions of potassium carbonate seems to be the only viable solution. The application of a water deluge system implies relying on break-up of the large water droplets by the accelerating explosion flame itself.